At Home In The Hills : Sense of Place in the Scottish Borders. - Gray, John (Berghahn Books, 2000)
To most outsiders, the hills of the Scottish Borders are a bleak and foreboding space - usually made to represent the stigmatized Other, Ad Finis, by the centers of power in Edinburgh, London, and Brussels. At a time when globalization seems to threaten our sense of place, people of the Scottish borderlands provide a vivid case study of how the being-in-place is central to the sense of self and identity. Since the end of the thirteenth century, people living in the Scottish Border hills have engaged in armed raiding on the frontier with England, developed capitalist sheep farming in.